Back to Living: Long-term Functional Status of Pediatric Patients Who Completed Intensive Interdisciplinary Pain Treatment. Issue 10 (October 2018) - Randall, Edin T.; Smith, Kelly R.; Conroy, Caitlin; Smith, Allison M.; Sethna, Navil; Logan, Deirdre E.
Abstract : Objectives: To provide a descriptive account of long-term functioning (≥5 y posttreatment) among youth who completed intensive interdisciplinary pain treatment (IIPT) for pediatric chronic pain conditions. Materials and Methods: A total of 95 patients (mean age at follow-up=20.0 y) treated at least 5 years previously at a single IIPT program completed questionnaires assessing pain, functional disability, health care utilization, academic/career achievement, and quality of life. Data analyses focused on pain, functioning, and progress toward developmental goals at long-term follow-up. Results: The majority of respondents report significant reduction in pain compared with preadmission ( P <0.001). Five years posttreatment, average functional disability scores were in the minimal range, with statistically significant decrease in functional disability from time of admission ( P <0.001). Nearly 80% of respondents characterized themselves as having no functional difficulties at follow-up. Clinically significant improvement was established for both pain and function. Respondents generally reported developmentally appropriate status, with 89% graduating high school on schedule. Discussion: Results show long-term positive functioning among individuals who underwent intensive rehabilitation treatment for chronic pain as children or adolescents. Despite experiencing one or more pain flares at some point after treatment, most former IIPT patients report minimal to no ongoing functional disability, complete or partial resolution of pain symptoms, and developmentally appropriate progress toward goals (eg, school completion, independent living).